Analysis of Differentiation Strategies in Increasing Company Competitiveness in the Retail Industry - Putra, Iman Ipraja; Kadir, Rahman; Munizu, Musran (PT. Riset Press International, 2023)
Review and analyze impact of differentiation strategy product, differentiation strategy services, and differentiation strategy image of Alfa Retailindo (Carrefour) to Power competitive company on business retail in Makassar City to be objective main study this. People who shop at PT Alfa Retailindo (Carrefour) in 2023 will become subject study this. In study this, questionnaire sent to participant for gather information. There are 100 participants in survey used for compile study this. Analysis done with use regression double using SPSS 25. The results show that third type differentiation product, service and image role positive and significant in a manner statistics in increase Power competitive company industry retail PT. Alfa Retailindo (Carrefour). Findings show that Power competitive company increase along with growth differentiation product, differentiation service, and differentiation image.